Chipko: Relasionalitas Perempuan “Liyan” dalam Etika Ekofeminisme Berdasarkan Pemikiran Komparatif Vandana Shiva dan Armada Riyanto - Kevin, Alfredo (Jurnal Ekologi, Masyarakat dan Sains, 2023)
Abstract: This research study pays attention to ecofeminism in the Chipko movement. The methodology used in this study is a comparative approach. An ecofeminist figure, Vandana Shiva has a perspective of an important relation between women and nature. Armada Riyanto calls nature as an other that must be treated as a subject as well as a society that must be respected, valued, and protected. As for nature as a metaphor for the essence of human life itself. The purpose of this study is that the Chipko movement is a symbol of local wisdom to use conscience in saving the existence of living things. The writer finds that nature provides an illustration of the existence of an important relationship between humans humans, nature and God. Armada refers to this dimension as the focus on transcendence. As a result, both Vandana Shiva’s and Armada Riyanto’s thoughts agree that conscience embodied in empathy plays an important role in efforts to care for and save the natural environment, as well as to stop paternalist thought that always dominate women, while women contain the concept of a mother who has love and great attention to their children, in this case is the forest.